Letter to the editor - Cormedi, Marina Candido Visontai; Folgueira, Maria Aparecida Azevedo Koike (Revista de Medicina, 2017)
Gastric cancer is an important cause of cancer death worldwide and in Brazil. Given the recent studies on this disease's mortality and survival rates in our country, we offer a view on future research possibilities.